Evaluating the effect of ashwagandharishta on human respiratory system by utilizing spirometry (Jahangirnagar University Journal of Biological Sciences, 2024)
The key objective of this present study is to analyze the effect(s) of Ashwagandharishta on the lung function of human males. After completing the 45 days of study, the parameter FVC decreased by 3.315 % than the initial period of the study of the control group. On the other hand, the parameters FEV1, FVFC, PEF, FEF25–75%, MEF 75%, MEF 50% and MEF 25% level was increased by 0.2951 %, 5.600 %, 0.971 %, 4.137 %, 1.909 %, 4.590 %, 5.777 %, 7.182 % and 10.635 % respectively after the 45 days of study than the initial period of the control group. Here no result was statistically significant. After the Chronic administration of Ashwagandharishta (ASG) to human male subjects for 45 days, the values of the parameters FVC, FEV1, FVFC, PEF, FEF25–75%, MEF 75% and MEF 50% was decreased by 4.109 %, 5.351 %, 1.077 %, 16.042 %, 7.199 % and 21.074 % respectively than the values of the initial period of the study of the ASG treated group. On the other hand, the parameter MEF 25% level was increased by 2.202 % after the 45 days chronic administration of the ASG. No result was statistically significant.Jahangirnagar University J. Biol. Sci. 12(1 & 2): 45-53, 2023 (June & December)